2023
DOI: 10.1136/bmjsem-2022-001489
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviours, menstrual history and the athletic career: a retrospective survey from adolescence to adulthood in female endurance athletes

Abstract: AimTo evaluate differences in menstrual and pubertal history and trends in eating behaviours among women with and without a competitive sports background. Additionally, we investigated if menstrual history and eating behaviours are associated with sports career-related factors.MethodsThis retrospective study was conducted on 100 women with a competitive endurance sports background and their age-matched, gender-matched and municipality-matched controls (n=98). Data were collected using a questionnaire using pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Moreover, we demonstrated herein that age at menarche is also influenced by discipline, with those athletes in the throwing subcategory having a mean age at menarche of 12.8, whereas endurance athletes had a significantly later age at menarche at 14.2 years. This is in line with a recent study which found the age of menarche in specifically endurance athletes was 14 years, compared to 12.5 in the non-athletic control group ( 20 ). This is of relevance given that delayed menarche can be a sign of REDs; the hypooestrogenic state may impair longterm bone health and have implications particularly from a sports injury perpesctive ( 4 , 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we demonstrated herein that age at menarche is also influenced by discipline, with those athletes in the throwing subcategory having a mean age at menarche of 12.8, whereas endurance athletes had a significantly later age at menarche at 14.2 years. This is in line with a recent study which found the age of menarche in specifically endurance athletes was 14 years, compared to 12.5 in the non-athletic control group ( 20 ). This is of relevance given that delayed menarche can be a sign of REDs; the hypooestrogenic state may impair longterm bone health and have implications particularly from a sports injury perpesctive ( 4 , 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…Studies in human populations exemplary of a negative energy balance have shed light on aberrant menstrual patterns. Ballet dancers [ 15 , 16 ] and athletes [ 17 , 18 ] engaged in high physical activity may have a delayed pubertal onset. Additionally, disordered eating, excessive exercise, or lifestyle stressors can cause menses loss in erstwhile normal-ovulatory women [ 19–22 ].…”
Section: Close Ties Between Nutritional Status and Female Reproductiv...mentioning
confidence: 99%